1960
DOI: 10.1111/j.1365-2494.1960.tb00183.x
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Nutrient Losses and Efficiency of Conserving Herbage as Silage, Barn‐dried Hay and Field‐cured Hay

Abstract: A review of American literature indicates that barn drying of hay and silage making are both greatly superior to the field curing of hay in preserving nutrients. This is true of total dry matter, crude protein, ether extract and ash; crude-fibre losses are greater in silage making. Energy losses run parallel with dry matter. Bam drying of hay with heat preserves a rather greater proportion of nutrients than does silage making.Chemical composition and digestibility are mostly a function of stage of maturity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1
2

Year Published

1965
1965
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 13 publications
1
14
1
2
Order By: Relevance
“…The only exceptions to this trend were crude-protein and trueprotein losses in the tedded hay, and the ash loss in the barn-dried hay in Expt 1. Carter (2) in a review of American work, found that with both barn-drying and swath-drying there was a greater loss of crude protein relative to dry matter, but the loss of other constituents followed the same trends as were observed in the present experiments. Murdoch and Bare (5) in an experiment in which grass was cut by a forage-harvester also found a greater loss of crude protein relative to dry matter.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The only exceptions to this trend were crude-protein and trueprotein losses in the tedded hay, and the ash loss in the barn-dried hay in Expt 1. Carter (2) in a review of American work, found that with both barn-drying and swath-drying there was a greater loss of crude protein relative to dry matter, but the loss of other constituents followed the same trends as were observed in the present experiments. Murdoch and Bare (5) in an experiment in which grass was cut by a forage-harvester also found a greater loss of crude protein relative to dry matter.…”
Section: Discussionsupporting
confidence: 82%
“…In contrast to these findings, Shepperson, Grundey and Wickens (10) found that crimping followed by tedding had no adverse effect on yield when compared with tedding only. The value of barn-drying in reducing drymatter losses in haymaking has been reviewed by Carter (2). He found that most results indicated a general superiority of barn-drying over field-curing in reducing dry-matter loss.…”
mentioning
confidence: 99%
“…The wilting time was short and was the same for all forage mixtures in this experiment (3 h). The short wilting time and the good weather conditions during wilting, without any precipitation, contributed to only small losses of α‐tocopherol and no losses of β‐carotene, as losses are dependent on the wilting time and weather conditions, and rain increases the losses (Carter, 1960; Ballet et al. , 2000).…”
Section: Discussionmentioning
confidence: 99%
“…, 2000). Carter (1960) reported losses of β‐carotene in hay of 80–90% and in silage of 40–60% from cutting to feeding. Nozière et al.…”
Section: Introductionmentioning
confidence: 99%
“…Terminating fleld exposure at this level and either flnishing the drying process by artiflcial ventilation or preventing deterioration by the application of a crop preservative reduces such losses. The information available on nutrient losses from American sources has already been reviewed (14). Conditioning decreases watersoluble carbohydrate losses compared with traditional treatment during favourable drying weather, but increases them in rainy weather.…”
Section: Dry-matter and Nutrient Lossesmentioning
confidence: 99%